Análise da política de incentivos fiscais da SUDENE sobre indicadores do mercado de trabalho dos municípios - Braz, Marleton Souza (2023)
The National Policy for Regional Development (PNDR) aims at local development and the reduction of intra- and inter-regional inequalities, and, for this, it counts as one of its financing instruments the tax incentives of reduction of the Corporate Income Tax (IRPJ) administered by the Superintendence of Development of the Northeast (Sudene). These incentives stimulate productive capital by deducting tax payments from legal entities in exchange for private investments. In view of this, this dissertation initially sought to analyze tax incentives and benefits, including their spatial distribution within the Sudene territory. For this purpose, an exploratory analysis of the data on approvals of this tax instrument was carried out. The next step was to check if the reduction in IRPJ affects labor market indicators at the municipal level. At this stage, the empirical strategy involved comparing the municipalities using a differencein- differences estimator developed by Callaway and Sant'Anna (2021), which allows to identify variations in the effect as the term of the incentive passes, as well as heterogeneous effects for each year after the incentive was granted to the first group of municipalities. From the exploratory analysis, it was observed that among the incentives administered by Sudene, the 75% reduction in Corporate Income Tax (IRPJ) was the most demanded after to primarily promote investments in modernization and establishment of companies, predominantly in the manufacturing and infrastructure sectors. However, the benefiting enterprises are concentrated in the coastal region of the Sudene area, where the capitals and metropolitan regions are located, which, therefore, are not priority areas for the National Regional Development Plan (PNDR), namely the semi-arid region andmunicipalities with lower income levels. In turn, the evaluation results show that the tax incentive increases municipal employment and income by 4.3% and 1.2%, respectively, whose effect is growing and appears in the early years. The effect is concentrated in smaller and less developed municipalities, which may contribute to reducing intra-regional inequalities.